Production Budget in Iraqi Historical Theatrical Performance: The Guardian Fate as an Example - Ahmed Hassan Al-Jubouri, Bassem Muhammad (Journal of Tikrit University for Humanities, 2025)
The technical procedure of any manufacturing process is closely linked to its management and planning. Understanding the dynamic nature of the process helps keep pace with the numerous daily changes. Therefore, it is essential to assess production potential as early as possible to enhance results. Theatrical productions that do not have balanced production lines are prone to multiple problems, including failure to achieve targets, significant time wastage, and poor performance, leading to wasted effort and negative consequences. Other productions that require a theater are also considered when balancing the entire production system and production line. The term "production line balancing" is used to describe the organization of a production budget, not just a specific task. This term is undoubtedly linked to production success. Failure to achieve this can lead to imbalance, which can lead to confusion, time wastage, and ultimately failure. Therefore, it is essential to pay attention to production budgets, especially in the case of expensive historical dramas. This study consists of four sections. The first section examines the theoretical framework. The researchers define the research question and its necessity, concluding with the following question: "Taking the historical tale of Iraq, The Guardian Fate, as an example, what is a production budget?" In addition to highlighting the importance of the study itself which is an economic study with significant implications for management and the artistic production process, particularly theatrical production. The research discusses the purpose and limitations of the study. The second section deals with the theoretical framework. It is divided into two subsections. The first discusses the concepts of budget and production in artistic endeavors and their importance in planning and preparing artistic and theatrical projects. The second, discusses the most important characteristics of management and production in theatrical performance. Section three examines the research procedures, including the study population, the selected samples, the reasons for their selection, and the methodology used to describe them. Section four includes the final results of the research, in addition to proposals and recommendations.